6a. By the convolution theorem,
![L\{t^3\star e^{5t}\} = L\{t^3\} \times L\{e^{5t}\} = \dfrac6{s^4} \times \dfrac1{s-5} = \boxed{\dfrac5{s^4(s-5)}}](https://tex.z-dn.net/?f=L%5C%7Bt%5E3%5Cstar%20e%5E%7B5t%7D%5C%7D%20%3D%20L%5C%7Bt%5E3%5C%7D%20%5Ctimes%20L%5C%7Be%5E%7B5t%7D%5C%7D%20%3D%20%5Cdfrac6%7Bs%5E4%7D%20%5Ctimes%20%5Cdfrac1%7Bs-5%7D%20%3D%20%5Cboxed%7B%5Cdfrac5%7Bs%5E4%28s-5%29%7D%7D)
6b. Similarly,
![L\{e^{3t}\star \cos(t)\} = L\{e^{3t}\} \times L\{\cos(t)\} = \dfrac1{s-3} \times \dfrac s{1+s^2} = \boxed{\dfrac s{(s-3)(s^2+1)}}](https://tex.z-dn.net/?f=L%5C%7Be%5E%7B3t%7D%5Cstar%20%5Ccos%28t%29%5C%7D%20%3D%20L%5C%7Be%5E%7B3t%7D%5C%7D%20%5Ctimes%20L%5C%7B%5Ccos%28t%29%5C%7D%20%3D%20%5Cdfrac1%7Bs-3%7D%20%5Ctimes%20%5Cdfrac%20s%7B1%2Bs%5E2%7D%20%3D%20%5Cboxed%7B%5Cdfrac%20s%7B%28s-3%29%28s%5E2%2B1%29%7D%7D)
7. Take the Laplace transform of both sides, noting that the integral is the convolution of
and
.
![\displaystyle f(t) = 3 - 4 \int_0^t e^\tau f(t - \tau) \, d\tau](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%28t%29%20%3D%203%20-%204%20%5Cint_0%5Et%20e%5E%5Ctau%20f%28t%20-%20%5Ctau%29%20%5C%2C%20d%5Ctau)
![\implies \displaystyle F(s) = \dfrac3s - 4 F(s) G(s)](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdisplaystyle%20F%28s%29%20%3D%20%5Cdfrac3s%20-%204%20F%28s%29%20G%28s%29)
where
. Then
, and
![F(s) = \dfrac3s - \dfrac4{s-1} F(s) \implies F(s) = \dfrac{\frac3s}{\frac{s+3}{s-1}} = 3\dfrac{s-1}{s(s+3)}](https://tex.z-dn.net/?f=F%28s%29%20%3D%20%5Cdfrac3s%20-%20%5Cdfrac4%7Bs-1%7D%20F%28s%29%20%5Cimplies%20F%28s%29%20%3D%20%5Cdfrac%7B%5Cfrac3s%7D%7B%5Cfrac%7Bs%2B3%7D%7Bs-1%7D%7D%20%3D%203%5Cdfrac%7Bs-1%7D%7Bs%28s%2B3%29%7D)
We have the partial fraction decomposition,
![\dfrac{s-1}{s(s+3)} = \dfrac13 \left(-\dfrac1s + \dfrac4{s+3}\right)](https://tex.z-dn.net/?f=%5Cdfrac%7Bs-1%7D%7Bs%28s%2B3%29%7D%20%3D%20%5Cdfrac13%20%5Cleft%28-%5Cdfrac1s%20%2B%20%5Cdfrac4%7Bs%2B3%7D%5Cright%29)
Then we can easily compute the inverse transform to solve for f(t) :
![F(s) = -\dfrac1s + \dfrac4{s+3}](https://tex.z-dn.net/?f=F%28s%29%20%3D%20-%5Cdfrac1s%20%2B%20%5Cdfrac4%7Bs%2B3%7D)
![\implies \boxed{f(t) = -1 + 4e^{-3t}}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cboxed%7Bf%28t%29%20%3D%20-1%20%2B%204e%5E%7B-3t%7D%7D)
Answer:
A
Step-by-step explanation:
-5 i s greater than -2.
Nope that aint true
-2 is greater than -5 is correct since -2 is closer to the postivie numbers and zero.
-5 is farther so it is less than -2.
Answer:
Step-by-step explanation:
We have to find the points that are on the graph by finding the order pair (x, y) We are given the x value, so substitute x in the given equation f(x) and find y.
The graph is a line
Answer:
A
Step-by-step explanation:
Formula is y=(x-h) Where h is the number the function is moved left or right...since it is supposed to be moved right, then (x-9) should probably work
Answer:
The APR at which the money is borrowed, is approximately 651.79%
Step-by-step explanation:
The amount which one wishes to borrow for two weeks, P = $600
The amount of interest that one must pay back = $25 per $100 borrowed
Therefore;
The total interest on the $600 loan (borrowed) for two weeks = 25/100× $600 = $150
The number of days for which the amount was borrowed = 2 weeks = 14 days
The Annual Percentage Rate, APR is given as follows;
![APR = \left (\dfrac{\left (\dfrac{Interest \ Paid \ for \ the \ Loan \ duration}{The \ amount \ borrowed} \right )}{The \ number \ of \ days \ the \ amount \ was \ borrowed } \right ) \times 365 \times 100](https://tex.z-dn.net/?f=APR%20%3D%20%5Cleft%20%28%5Cdfrac%7B%5Cleft%20%28%5Cdfrac%7BInterest%20%5C%20Paid%20%5C%20for%20%5C%20the%20%20%5C%20Loan%20%5C%20duration%7D%7BThe%20%5C%20amount%20%5C%20borrowed%7D%20%5Cright%20%29%7D%7BThe%20%5C%20number%20%5C%20of%20%5C%20days%20%5C%20the%20%5C%20amount%20%5C%20was%20%20%5C%20borrowed%20%7D%20%5Cright%20%29%20%5Ctimes%20365%20%5Ctimes%20100)
Therefore, we get
![APR = \left (\dfrac{\left (\dfrac{150}{600} \right )}{14 } \right ) \times 365 \times 100 \approx 651.79 \%](https://tex.z-dn.net/?f=APR%20%3D%20%5Cleft%20%28%5Cdfrac%7B%5Cleft%20%28%5Cdfrac%7B150%7D%7B600%7D%20%5Cright%20%29%7D%7B14%20%7D%20%5Cright%20%29%20%5Ctimes%20365%20%5Ctimes%20100%20%20%5Capprox%20651.79%20%5C%25)
The annual rate at which the money is borrowed, APR ≈ 651.79%.